Explore IDNLearn.com's extensive Q&A database and find the answers you're looking for. Get thorough and trustworthy answers to your queries from our extensive network of knowledgeable professionals.
Sagot :
Let's solve it step by step:
### Part (i)
We need to evaluate the expression [tex]\(-\frac{2}{3} x^2 + 5x - 2\)[/tex] for [tex]\( x = -3 \)[/tex].
1. Substitute [tex]\( x = -3 \)[/tex] into the expression:
[tex]\[ -\frac{2}{3}(-3)^2 + 5(-3) - 2 \][/tex]
2. Calculate [tex]\((-3)^2\)[/tex]:
[tex]\[ (-3)^2 = 9 \][/tex]
3. Substitute [tex]\( 9 \)[/tex] back into the expression:
[tex]\[ -\frac{2}{3} \cdot 9 + 5(-3) - 2 \][/tex]
4. Calculate [tex]\(-\frac{2}{3} \cdot 9\)[/tex]:
[tex]\[ -\frac{2}{3} \cdot 9 = -6 \][/tex]
5. Calculate [tex]\( 5(-3) \)[/tex]:
[tex]\[ 5 \cdot -3 = -15 \][/tex]
6. Substitute these values back into the expression:
[tex]\[ -6 - 15 - 2 \][/tex]
7. Simplify the expression:
[tex]\[ -6 - 15 = -21 \][/tex]
[tex]\[ -21 - 2 = -23 \][/tex]
So, the value for part (i) is:
[tex]\[ -23.0 \][/tex]
### Part (ii)
We need to evaluate the expression [tex]\(\frac{3a + 2b - 5}{a + b}\)[/tex] for [tex]\(a = 2\)[/tex] and [tex]\(b = -1\)[/tex].
1. Substitute [tex]\( a = 2 \)[/tex] and [tex]\( b = -1 \)[/tex] into the expression:
[tex]\[ \frac{3 \cdot 2 + 2 \cdot (-1) - 5}{2 + (-1)} \][/tex]
2. Calculate [tex]\( 3 \cdot 2 \)[/tex]:
[tex]\[ 3 \cdot 2 = 6 \][/tex]
3. Calculate [tex]\( 2 \cdot (-1) \)[/tex]:
[tex]\[ 2 \cdot (-1) = -2 \][/tex]
4. Substitute these values back into the expression:
[tex]\[ \frac{6 - 2 - 5}{2 - 1} \][/tex]
5. Simplify the numerator:
[tex]\[ 6 - 2 = 4 \][/tex]
[tex]\[ 4 - 5 = -1 \][/tex]
6. Simplify the denominator:
[tex]\[ 2 - 1 = 1 \][/tex]
7. Divide the numerator by the denominator:
[tex]\[ \frac{-1}{1} = -1 \][/tex]
So, the value for part (ii) is:
[tex]\[ -1.0 \][/tex]
Therefore, the final answers are:
- (i) [tex]\(-23.0\)[/tex]
- (ii) [tex]\(-1.0\)[/tex]
### Part (i)
We need to evaluate the expression [tex]\(-\frac{2}{3} x^2 + 5x - 2\)[/tex] for [tex]\( x = -3 \)[/tex].
1. Substitute [tex]\( x = -3 \)[/tex] into the expression:
[tex]\[ -\frac{2}{3}(-3)^2 + 5(-3) - 2 \][/tex]
2. Calculate [tex]\((-3)^2\)[/tex]:
[tex]\[ (-3)^2 = 9 \][/tex]
3. Substitute [tex]\( 9 \)[/tex] back into the expression:
[tex]\[ -\frac{2}{3} \cdot 9 + 5(-3) - 2 \][/tex]
4. Calculate [tex]\(-\frac{2}{3} \cdot 9\)[/tex]:
[tex]\[ -\frac{2}{3} \cdot 9 = -6 \][/tex]
5. Calculate [tex]\( 5(-3) \)[/tex]:
[tex]\[ 5 \cdot -3 = -15 \][/tex]
6. Substitute these values back into the expression:
[tex]\[ -6 - 15 - 2 \][/tex]
7. Simplify the expression:
[tex]\[ -6 - 15 = -21 \][/tex]
[tex]\[ -21 - 2 = -23 \][/tex]
So, the value for part (i) is:
[tex]\[ -23.0 \][/tex]
### Part (ii)
We need to evaluate the expression [tex]\(\frac{3a + 2b - 5}{a + b}\)[/tex] for [tex]\(a = 2\)[/tex] and [tex]\(b = -1\)[/tex].
1. Substitute [tex]\( a = 2 \)[/tex] and [tex]\( b = -1 \)[/tex] into the expression:
[tex]\[ \frac{3 \cdot 2 + 2 \cdot (-1) - 5}{2 + (-1)} \][/tex]
2. Calculate [tex]\( 3 \cdot 2 \)[/tex]:
[tex]\[ 3 \cdot 2 = 6 \][/tex]
3. Calculate [tex]\( 2 \cdot (-1) \)[/tex]:
[tex]\[ 2 \cdot (-1) = -2 \][/tex]
4. Substitute these values back into the expression:
[tex]\[ \frac{6 - 2 - 5}{2 - 1} \][/tex]
5. Simplify the numerator:
[tex]\[ 6 - 2 = 4 \][/tex]
[tex]\[ 4 - 5 = -1 \][/tex]
6. Simplify the denominator:
[tex]\[ 2 - 1 = 1 \][/tex]
7. Divide the numerator by the denominator:
[tex]\[ \frac{-1}{1} = -1 \][/tex]
So, the value for part (ii) is:
[tex]\[ -1.0 \][/tex]
Therefore, the final answers are:
- (i) [tex]\(-23.0\)[/tex]
- (ii) [tex]\(-1.0\)[/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For trustworthy answers, visit IDNLearn.com. Thank you for your visit, and see you next time for more reliable solutions.